2013
DOI: 10.5153/sro.3000
|View full text |Cite
|
Sign up to set email alerts
|

‘Yobs’ and ‘Snobs’: Embodying Drink and the Problematic Male Drinking Body

Abstract: The cultural linkages between the drinking of alcohol and the assertion of masculinity have been well explored. In particular, drinking alcohol is still assumed to be a site where masculinity can be tested and proved. However, equally, drinking can be seen to undermine and discredit the male body. Further, older men's drinking practices are commonly overlooked. Through exploring two examples of cultural stereotypes relating to male drinking bodies, the lager lout and the real ale enthusiast, the article argues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Unrestrained conduct in others is greeted with repugnance and distaste and the use of terms such as 'horrible', 'cheap' and 'nasty'. In this, then, it is perhaps unsurprising that the unbounded and messy bodies of some drinkers have been a focal point in media debates about drinking and drunkenness in Britain (a theme also explored in Thurnell Read, 2011aRead, , 2013. In particular, bodies are central to classed discourses of disgust and distaste where the unruly classed body equates to moral or psychological failings of the individual (Lawler, 2005: Skeggs, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Unrestrained conduct in others is greeted with repugnance and distaste and the use of terms such as 'horrible', 'cheap' and 'nasty'. In this, then, it is perhaps unsurprising that the unbounded and messy bodies of some drinkers have been a focal point in media debates about drinking and drunkenness in Britain (a theme also explored in Thurnell Read, 2011aRead, , 2013. In particular, bodies are central to classed discourses of disgust and distaste where the unruly classed body equates to moral or psychological failings of the individual (Lawler, 2005: Skeggs, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] A few studies have explored drinking cultures in male-dominated workplaces and found that drinking was considered to be a normal part of working life, and acceptance, and indeed any management intervention would be actively challenged by workers. 45,[47][48][49] Likewise, managers may be ambivalent to respond to these issues.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In addition, others have argued that beer consumption is central to homosocial bonding among men, a key component of "doing masculinity" (de Smith 2007a, 2007b;Eriksen 1999;McCracken 1993;Measham 2002;Thurnell-Read 2012;Wenner and Jackson 2009;West and Zimmerman 1987). This research corpus on beer and masculinity is truly expansive, but its limitations are twofold: these resounding conclusions that beer is masculine tend to reduce beer to lager; and by extension, this body of literature tends to restrict cultural analysis of beer to the mainstream beer culture, which is largely homosocial and univorous (for exceptions, see Chapman, Lellock, and Lippard 2017;Darwin 2017;Thurnell-Read 2013, 2016.…”
Section: The Masculinization Of Beermentioning
confidence: 99%